Social and Legal Conditionality of Deformation of Professional Legal Consciousness of Lawyers - V. S. Bredneva (Теоретическая и прикладная юриспруденция)
Structural elements of legal consciousness of lawyers can be deformed under the influence of various factors, which creates adverse consequences for the individual, the state and society. Law enforcers have the ability to reduce the impact of certain deforming factors, to prevent the risk of professional burnout, if the choice of professional legal activity (profession) will correspond to their moral ideas.